Urine colorimetry for therapeutic drug monitoring of pyrazinamide during tuberculosis treatment. (March 2018) - Zentner, Isaac; Modongo, Chawangwa; Zetola, Nicola M.; Pasipanodya, Jotam G.; Srivastava, Shashikant; Heysell, Scott K.; Mpagama, Stellah; Schlect, Hans P.; Gumbo, Tawanda; Bisson, Gregory P.; Vinnard, Christopher
Highlights: The objective was to determine whether a urine test can identify tuberculosis patients with adequate serum pyrazinamide exposures. The urine colorimetric assay was 97% sensitive and 50% specific to identify HIV/tuberculosis patients with pharmacokinetic target attainment, with an area under the receiver operating characteristics curve of 0.81 (95% confidence interval 0.60–0.97). Future work will focus on refinement of the approach, with the goal of developing a simple, point-of-care test that could be available for therapeutic drug monitoring during anti-tuberculosis therapy in high-burden settings. Abstract: Objectives: Pyrazinamide is a key drug in the first-line treatment regimen for tuberculosis, with a potent sterilizing effect. Although low pyrazinamide peak serum concentrations ( C max ) are associated with poor treatment outcomes, many resource-constrained settings do not have sufficient laboratory capacity to support therapeutic drug monitoring (TDM). The objective of this study was to determine whether a colorimetric test of urine can identify tuberculosis patients with adequate pyrazinamide exposures, as defined by serum C max above a target threshold. Methods: In the derivation study of healthy volunteers, three dose sizes of pyrazinamide were evaluated, and intensive pharmacokinetic blood sampling was performed over an 8-h period, with a timed urine void at 4 h post-dosing. Pyrazinamide in urine was isolated by spin column centrifugation with an exchange resin, followed by colorimetric analysis; the absorbance peak at 495 nm was measured. The urine assay was then evaluated in a study of 39 HIV/tuberculosis patients in Botswana enrolled in an intensive pharmacokinetic study. Receiver operating characteristics (ROC) curves were used to measure diagnostic accuracy. The guideline-recommended pyrazinamide serum C max target of 35 mg/l was evaluated in the primary analysis; this target was found to be predictive of favorable outcomes in a clinical study. Following this, a higher serum C max target of 58 mg/l was evaluated in the secondary analysis. Results: At the optimal cut-off identified in the derivation sample, the urine colorimetric assay was 97% sensitive and 50% specific to identify 35 of 39 HIV/tuberculosis patients with pharmacokinetic target attainment, with an area under the ROC curve of 0.81 (95% confidence interval 0.60–0.97). Diagnostic accuracy was lower at the 58 mg/l serum C max target, with an area under the ROC curve of 0.68 (95% confidence interval 0.48–0.84). Men were less likely than women to attain either serum pharmacokinetic target. Conclusions: The urine colorimetric assay was sensitive but not specific for the detection of adequate pyrazinamide pharmacokinetic exposures among HIV/tuberculosis patients in a high-burden setting.